2017
DOI: 10.1093/icvts/ivx368
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-matched analysis of outcomes after mitral valve surgery between trainees and consultants (institutional report)

Abstract: Mitral valve surgery can be safely performed by trainees and provides similar short- and long-term results compared with consultant surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The incidence of postoperative neurological complications was also smaller in the repair group but in this case, there was no significant difference between the groups. A meta-analysis previously published concluded that elderly patients who receive MVr have better early outcomes than those undergoing MVR 20 : with our meta-analysis, including more recent studies, we confirm these conclusions. Another important finding of our study was a significant advantage for the MVr in terms of survival rates over the long term:…”
Section: Operative Surgical Timessupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of postoperative neurological complications was also smaller in the repair group but in this case, there was no significant difference between the groups. A meta-analysis previously published concluded that elderly patients who receive MVr have better early outcomes than those undergoing MVR 20 : with our meta-analysis, including more recent studies, we confirm these conclusions. Another important finding of our study was a significant advantage for the MVr in terms of survival rates over the long term:…”
Section: Operative Surgical Timessupporting
confidence: 88%
“…In terms of operative timings, we found no evidence of prolonged surgical times when performing a repair although this is not consistent across the different studies. Indeed, MV repair is becoming the standard treatment for MV disease and more centers are conducting repairs routinely with improvements in operative timings and outcomes 21 . It has to be noted that a previously published randomized study 22 showed a prolonged CPB and cross‐clamp time in the repair group, and the authors suggested that this was the leading cause for a prolonged ventilatory support 22 .…”
Section: Discussionmentioning
confidence: 99%
“…There were no mortality differences between TS and FTS. The in‐hospital mortality for TS is reported as 2% versus 6% in FTS cohorts 24–26 …”
Section: Resultsmentioning
confidence: 99%
“…3 It is also challenging for the institutions responsible for the training programs, since they are expected to offer an efficient and adequate curriculum, which relies on a paradox of providing safe surgical opportunity without compromising the postoperative outcomes and excellent patient care. 4 Operating room surgical training has significant limitations indeed, considering it provides short time to develop technical skills and has low tolerance for learning mistakes. In this context, we believe that incorporating simulation on biological models in our residency program could improve cardiovascular surgical training and patient safety, due to its potentiality to avoid surgical technical failure that would compromise the outcomes, bringing more safety, efficacy, and better results in the longer term.…”
Section: Introductionmentioning
confidence: 99%
“…It is also challenging for the institutions responsible for the training programs, since they are expected to offer an efficient and adequate curriculum, which relies on a paradox of providing safe surgical opportunity without compromising the postoperative outcomes and excellent patient care 4 . Operating room surgical training has significant limitations indeed, considering it provides short time to develop technical skills and has low tolerance for learning mistakes.…”
Section: Introductionmentioning
confidence: 99%